Water, sanitation, and hygiene access in Senegal and its impact on the occurrence of diarrhea in children under 5 years old - Mouhamadou Lamine Daffe; Cheikh Diop; Bonheur Dounebaine; Samba Sagor Diop; Jessica Carmelia Mbemba Peleka; Fatoumata Bah; Salimata Thiam; Awa Ndong; Mathilde Cabral; Aminata Toure; Absa Lam; Mamadou Fall (IWA Publishing, 2022)
Diarrheal diseases are the second leading cause of child mortality worldwide, occurring in about one in every nine child deaths, and were associated with water, sanitation, and hygiene (WASH) access. In this study, we provided an overview of WASH indicators' evolution from 2000 to 2017 and their impact on the occurrence of diarrhea in children under 5 years old in Senegal. It was a retrospective cross-sectional study, in which we did a secondary analysis of data from the Joint Monitoring Program (JMP) for water supply and sanitation and from the Senegal Demographic and Health Survey 2018. Our results showed that access to safely managed services increased by 18.1 and 19.1%, respectively, for water and sanitation. The prevalence of diarrhea estimated at 18.16% was associated with straining water through a cloth (adjusted odds ratio (AOR) [95% confidence interval (CI)]: 1.21 [1.00-1.45]) and getting water supplies from a source not located in a dwelling (AOR [95% CI]: 1.59 [1.21-2.09]). The prevalence of diarrhea among children under 5 years old was still relatively high in Senegal and was significantly associated with a lack of WASH access. Although the latter continues to increase, additional efforts to make water safer to drink will significantly reduce the occurrence of diarrheal diseases among children under 5 years old in Senegal. HIGHLIGHTS WASH access has improved in recent years; however, the prevalence of diarrhea is still relatively high.; Diarrhea is associated with a lack of WASH access. Indeed, straining water through a cloth and getting water supplies from a source not located in a dwelling are associated with an excess risk of diarrhea among children under 5 years old.; Interventions to improve WASH are opportunities to save lives and are cost-effective measures.;